2016
DOI: 10.1002/jbm.b.33775
|View full text |Cite
|
Sign up to set email alerts
|

Substitutional limit of gadolinium inβ‐tricalcium phosphate and its magnetic resonance imaging characteristics

Abstract: To compensate the limitations of bone tissue magnetic resonance imaging (MRI), a series of gadolinium (Gd ) substituted β-Tricalcium phosphate [β-TCP, β-Ca (PO ) ] were developed. All the powders were characterized using XRD, Raman spectroscopy, Rietveld refinement of the XRD data and the studies confirmed the Gd occupancy at Ca (1), Ca (2) and Ca (3) lattice sites of β-Ca (PO ) HR-TEM analysis revealed the spherical nature of particles with diameter about 100 nm. The Gd doped β-Ca (PO ) exhibited non-toxic be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
(80 reference statements)
3
20
0
Order By: Relevance
“…On the contrary, the expansion of β‐Ca 3 (PO 4 ) 2 lattice is obvious in the order of 1GZCaP and 2GZCaP and thereafter establishes a stable state in other compositions. The substitution limit of RE 3+ in β‐Ca 3 (PO 4 ) 2 has been reported in previous studies and in particular the saturation limit of Gd 3+ has been reported as 4.38 mol‐% . Gd 3+ exceeding this substitution limit crystallizes as GdPO 4 in calcium phosphate systems.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…On the contrary, the expansion of β‐Ca 3 (PO 4 ) 2 lattice is obvious in the order of 1GZCaP and 2GZCaP and thereafter establishes a stable state in other compositions. The substitution limit of RE 3+ in β‐Ca 3 (PO 4 ) 2 has been reported in previous studies and in particular the saturation limit of Gd 3+ has been reported as 4.38 mol‐% . Gd 3+ exceeding this substitution limit crystallizes as GdPO 4 in calcium phosphate systems.…”
Section: Discussionsupporting
confidence: 62%
“…The substitution limit of RE 3+ in -Ca 3 (PO 4 ) 2 has been reported in previous studies and in particular the saturation limit of Gd 3+ has been reported as 4.38 mol-%. [24] Gd 3+ exceeding this substitution limit crystallizes as GdPO 4 in calcium phosphate systems. Moreover, Gd 3+ has been reported to occupy the Ca 2+ (1), Ca 2+ (2) and Ca 2+ (3) sites of -Ca 3 (PO 4 ) 2 lattice, a result that is also witnessed in the current investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…β-TCP powder (Beta TCP; Tomita Pharmaceutical, Naruto, Japan) was pulverized into nano-sized particles using a pulverizer (Nanomizer, Yokohama, Japan). The peak profile of β-TCP powder via X-ray diffraction investigations was overlapped with the data of the previous report 27,32) . The β-TCP nanoparticles, along with the surfactant sodium cholate (0.2 wt%), were then dispersed in 1-methyl-2-pyrrolidone (Wako Pure Chemical Industries, Osaka, Japan).…”
Section: Fabrication and Characterization Of β-Tcp Nanoparticlemodifimentioning
confidence: 73%
“…The RE 3+ incorporation is mainly due to the attractive optical and magnetic features displayed by these elements in biomedicine . RE 3+ substitution in ZrO 2 has been an extensive study that enumerates the positive impact in the resultant structure such as to accommodate a wide range of either individual or multiple RE 3+ substitutions devoid of significant structural distortion . It has been deduced that depending on the concentration of RE 3+ substitution in increasing order, a gradual phase transition in the order of tetragonal ( t ‐ZrO 2 ) to cubic ZrO 2 ( c ‐ZrO 2 ) and thereafter the formation of pyrochlore structure are witnessed .…”
Section: Introductionmentioning
confidence: 99%